Motion Style Acupuncture Can Effectively Improve the Effectiveness of Acute Nonspecific Low Back Pain: a Meta-analysis - FEI Jingwen, LIN Huize, ZHANG Pingping, LIU Lanping, WANG Xiang, SHEN Jianghong, ZHU Kexin, YANG Tao, YU Jinna (Zhongguo quanke yixue, 2023)
Background Many randomized controlled trials (RCTs) about motion style acupuncture in the treatment of acute nonspecific low back pain (ANSLBP) have been published recently, but there is no new systematic evaluation for effectiveness and safety of this treatment in ANSLBP. Objective To systematically evaluate the effectiveness and safety of motion style acupuncture in treating ANSLBP by meta-analysis. Methods RCTs, crossover studies or cohort studies about effectiveness and safety of motion style acupuncture in treating ANSLBP were retrieved in electronic databases of CNKI, CBM, Wanfang Data, VIP, PubMed, the National Library of Medicine, Embase and the Cochrane Central Register of Controlled Trials from inception to March 25th, 2021. Revman 5.3 was used to complete the Meta-analysis. Results All the finally enrolled 17 articles used a design of RCT, including 1 226 patients, and 610 of them were treated with motion style acupuncture (observation group) , and other 616 patients were treated with positive control, blank control, placebo acupuncture or dummy acupuncture (control group) . Meta-analysis showed that, compared with controls treated with Western medicine, the observation group had significantly lower post-treatment VAS score〔MD=-1.54, 95%CI (-2.43, -0.65) , P=0.000 7〕, and Roland-Morris Disability Questionnaire (RMDQ) score〔MD=-3.08, 95%CI (-4.92, -1.24) , P=0.001〕, and significantly higher post-treatment ROM of lumbar vertebra〔MD=-1.42, 95%CI (-1.62, -1.22) , P<0.000 01〕and overall response rate〔RR=1.27, 95%CI (1.19, 1.35) , P<0.000 01〕, but there was no significant difference in post-treatment ODI score between the two groups〔MD=-5.11, 95%CI (-19.12, 8.91) , P=0.48〕. Compared with controls treated with dummy acupuncture, the observation group had significantly lower post-treatment VAS score〔MD=-1.70, 95%CI (-2.05, -1.35) , P<0.000 01〕and RMDQ score〔MD=-3.06, 95%CI (-4.50, -2.70) , P<0.000 01〕. Compared with controls treated with physical therapy, the observation group had significantly lower post-treatment VAS score〔MD=-1.60, 95%CI (-2.06, -1.14) , P<0.000 01〕and RMDQ score〔MD=-3.00, 95%CI (-4.31, -1.69) , P<0.000 01〕. Compared with controls treated with Tuina, the observation group had significantly lower post-treatment VAS score〔MD=-1.50, 95%CI (-1.65, -1.35) , P<0.000 01〕, and significantly higher overall response rate〔RR=1.19, 95%CI (1.09, 1.30) , P=0.000 1〕. Only one RCT reported that the incidence of adverse events in observation group was 13.33% (4/30) during treatment. Conclusion Available documentary evidence showed that, motion style acupuncture can effectively relieve the pain and lumbar dysfunction, and improve the ROM of lumbar vertebra and overall response rate in patients with ANSLBP, with high safety, but which still needs to be confirmed by more high-quality, large-sample RCTs.